Kinerja Keuangan dan Nilai Perusahaan Sektor Farmasi - Marcellia Susan; Jacinta Winarto (Jurnal Informatika Ekonomi Bisnis, 2023)
Companies have goals to be achieved. The company's efforts aim to produce sound financial performance and increase firm value. Many factors can determine the value of a company. This research aims to obtain a depiction of the performance and value of the company. In addition, testing and analyzing the influence of financial performance factors on firm value is also the aim of this study. The research sample is pharmaceutical sector companies listed on the Indonesia Stock Exchange. Secondary data was obtained from financial statements for five years and processed using regression analysis. The results showed that the indicators measuring liquidity, leverage, activity, profitability, and company size contributed to determining firm value. Specifically, the test results show that the ability of pharmaceutical companies to meet current liabilities as the maturity date is a factor determining firm value.